Some rights of the child in Islam - Ahmed, Musalm Abdul Qader (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify some of the rights of the child in Islam, and to show that the performance of these rights is at the core of the commitment to the directives of the Islamic religion with emphasis on the primacy of Islam in the field of childhood and in the development of clear rights for the child. The study followed the descriptive approach through analyzing content content, The study has many results, the most important of which is that the child has a high status in Islam and has rights before and after his birth, beginning with choosing the husband and then establishing the adhaan and performing prayer in his ears immediately after his birth. He also has the right to breastfeed and choose a good name for him. Children in one family As well as the right to play, recreation, and the right to inheritance, the right to care for the orphan child, the study recommends that the provision of children's rights, and conduct further research in the field of childhood in Islam and Islamic education.
Keywords: rights; children; childhood; Islam; family